Sintering properties and microstructure of NiMn2O4-silver composites - Piyaporn Jaimeewong (2018)
Sintering properties, phase and microstructure of nickel mangante-silver composites were studied. Nickel manganite (NiMn 2 O 4 ) powder, synthesized by solid state coordination, was mixed with silver particles by ball milling for 21 h. NiMn 2 O 4 -xAg (when x = 0, 3, 6, 9, 12 and 15 wt%) ceramic composites with pellet diameter of 1 cm were fabricated by uniaxial pressing (1 ton) and subsequent cold isostatic pressing (170 MPa) and then sintered at 1200°C for 3 h. NiMn 2 O 4 ceramics have 97% relatively density. It was found that some Ag particles may evaporate from the surface of NiMn 2 O 4 -xAg composites. Decreasing of shrinkage as Ag content increases may be due to porosity occurred by Ag evaporation at high temperature and coalescence of Ag agglomerated particles. No chemical reaction between NiMn 2 O 4 and Ag particle was observed by X-ray diffraction. Dispersion of Ag particles in NiMn 2 O 4 matrix was revealed. It is found that Ag particles agglomerate into larger size particles when the amount of Ag increases. Resistivity at room temperature of NiMn 2 O 4 is dramatically decreases by 3 wt%Ag addition. © 2013 Copyright Taylor and Francis Group, LLC.